New Forms of Regional Inequalities in Greece: the Diffusion of the Internet Across Greek Regions - Sophia Skordili (European Regional Science Association (ERSA), 2006)
A large number of studies dealing with the evolution of regional inequalities in Greece insist to make use of improper and outdated indices. Indices such as the number of telephone lines per capita and electricity consumption per capita were suitable to describe regional inequalities during the previous decades however, nowadays, they present insignificant regional variations. Among others, the diffusion of the internet to greek regions, is a useful indication of their growth potential and technological capacity. There is no doubt that internet can powerfully influence individuals, places, societies and economies and these effects are likely to grow over the foreseeable future. Primary data show that there is a notable imbalance at national level in terms of per capita usage levels. The disparity of the internet access around the country has given rise to the issue of a national digital divide. This paper investigates and maps the differences in the internet penetration rate to population and businesses across Greek regions and proceeds to a preliminary identification of the determinants of this unequal Geography. Data limitations, and paucity of earlier research make this a challenging task.
Keywords: 330